2021
DOI: 10.1523/eneuro.0500-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Accurate Substrate Processing with Distinct Presenilin/γ-Secretases in Human Cortical Neurons

Abstract: Mutations in the presenilin genes (PS1, PS2) have been linked to the majority of familial Alzheimer's disease (AD). Although great efforts have been made to investigate pathogenic PS mutations, which ultimately cause an increase in the toxic form of β-amyloid (Aβ), the intrinsic physiological functions of PS in human neurons remain to be determined. In this study, to investigate the physiological roles of PS in human neurons, we generated PS1 conditional knockout induced pluripotent stem cells (iPSCs), in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 95 publications
7
23
0
Order By: Relevance
“…Although low signal intensities of Aβ42 prevented us to calculate reliable Aβ42/Aβ40 ratios from IP-MS measurements, qualitatively, Aβ42 levels relative to Aβ40 appeared to be similar for PS1 and PS2. This is in line with studies reporting a similar Aβ42/Aβ40 ratio for both PS paralogs ( 22 , 23 ) but inconsistent with other studies describing a higher Aβ42/Aβ40 ratio for PS2-containing γ-secretase ( 52 , 53 ). For both paralogs, ε49 appears to be the major cleavage site, followed by ε48, which agrees with previous reports ( 28 , 54 , 55 ).…”
Section: Discussionsupporting
confidence: 71%
“…Although low signal intensities of Aβ42 prevented us to calculate reliable Aβ42/Aβ40 ratios from IP-MS measurements, qualitatively, Aβ42 levels relative to Aβ40 appeared to be similar for PS1 and PS2. This is in line with studies reporting a similar Aβ42/Aβ40 ratio for both PS paralogs ( 22 , 23 ) but inconsistent with other studies describing a higher Aβ42/Aβ40 ratio for PS2-containing γ-secretase ( 52 , 53 ). For both paralogs, ε49 appears to be the major cleavage site, followed by ε48, which agrees with previous reports ( 28 , 54 , 55 ).…”
Section: Discussionsupporting
confidence: 71%
“…c-Secretase primarily processes APP C99 in acidic compartments of neurons While FRET/FLIM and super-resolution microscopy revealed closer proximity between APP and PSEN1 near and/or at the cell surface (Berezovska et al, 2003;Escamilla-Ayala et al, 2020), earlier biochemical studies suggested that Ab is generated rather in the endo-lysosomal compartments (Haass et al, 1992;Koo and Squazzo, 1994;Schrader-Fischer and Paganetti, 1996;Koo et al, 1996;Pasternak et al, 2003). Recent studies shed light on the restricted localization of PSEN2 in late endosomes and lysosomes (Meckler and Checler, 2016;Sannerud et al, 2016;Watanabe et al, 2021), and the role of PSEN2/g -secretase in the generation of intracellular Ab (Sannerud et al, 2016). To directly visualize where g -secretase processes C99 and thus generates Ab peptides, we employed high-resolution confocal microscopy and our recently developed C99 720-670 biosensor (Houser et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, g -secretase has a broad pH range and retains considerable activity at lower pHs. Furthermore, previous studies illustrated that, while PSEN1/g -secretase is broadly expressed within the entire cells, PSEN2/g -secretase is predominantly localized in late endosomes and lysosomes (Meckler and Checler, 2016;Sannerud et al, 2016;Watanabe et al, 2021). Therefore, we predict the prominent processing of C99 720-670 biosensor by g -secretase and the accumulation of Ab in these compartments could be because the actual expression of functional g -secretase complexes (i.e., PSEN1 "plus" PSEN2/ g -secretase) is higher in the acidic subcellular loci than other areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSEN1 is the proteolytic subunit of the γ-secretase complex which cleaves transmembrane proteins by initiating a wide range of indispensable biochemical processes and pathways. However, this complex also cleaves the transmembrane domain of the APP protein which produces the toxic and accumulative form of the amyloid-β-peptide (Aβ1-42) forming the characteristic plaque depositions in Alzheimer's disease (Takasugi et al, 2003;Watanabe et al, 2021). Besides its plasma membrane localization, PSEN1 is also present in the endoplasmic reticulum, where it is responsible for posttranslational endoproteolytic processing by cleaving the N-or C-terminal fragments (NTF or CTF, respectively) of various proteins (Wolfe, 2019).…”
Section: Alzheimer's Diseasementioning
confidence: 99%